Peroxisome Proliferator–Activated Receptors and The Metabolic Syndrome - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Obesity is a growing threat to global health by virtue of its association with insulin resistance, inflammation, hypertension, and dyslipidemia, collectively known as the metabolic syndrome (MetS). The nuclear receptors PPARα and PPARγ are therapeutic targets for hypertriglyceridemia and insulin resistance, respectively, and drugs that modulate these receptors are currently in clinical use. More recent work on the PPARδ has uncovered a dual benefit for both hypertriglyceridemia and insulin resistance, highlighting the broad potential of PPARs in the treatment of metabolic disease.CONTENT: We have learned much about PPARs, the metabolic fat sensors, and the molecular pathways they regulate. Through their distinct tissue distribution and specific target gene activation, the three PPARs together control diverse aspects of fatty acid metabolism, energy balance, insulin sensitivity glucose homeostasis, inflammation, hypertension and atherosclerosis. These studies have advanced our understanding of the etiology for the MetS. Mechanisms revealed by these studies highlight the importance of emerging concepts, such as the endocrine function of adipose tissue, tissue-tissue cross-talk and lipotoxicity, in the pathogenesis of type 2 diabetes mellitus and CVD.SUMMARY: The elucidation of key regulators of energy balance and insulin signaling have revolutionized our understanding of fat and sugar metabolism and their intimate link. The three ‘lipidsensing’ (PPARα, PPARγ and PPARδ) exemplify this connection, regulating diverse aspects of lipid and glucose homeostasis, and serving as bonafide therapeutic targets.KEYWORDS: Peroxisome Proliferator, Activated Receptor, Metabolic Syndrome